2006
DOI: 10.1016/j.bbadis.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Dose ranging and efficacy study of high-dose coenzyme Q10 formulations in Huntington's disease mice

Abstract: There is substantial evidence that a bioenergetic defect may play a role in the pathogenesis of Huntington's Disease (HD). A potential therapy for remediating defective energy metabolism is the mitochondrial cofactor, coenzyme Q10 (CoQ10). We have reported that CoQ10 is neuroprotective in the R6/2 transgenic mouse model of HD. Based upon the encouraging results of the CARE-HD trial and recent evidence that high-dose CoQ10 slows the progressive functional decline in Parkinson's disease, we performed a dose rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 46 publications
6
79
1
2
Order By: Relevance
“…Recently, Smith et al (2006) have performed a dose ranging study administering co-enzyme Q 10 (an essential cofactor of the mitochondrial electron transport chain that can act as a potent antioxidant) in R6/2 mice. The treatment was initiated at postnatal day 28 and high doses of co-enzyme Q 10 significantly extended survival in R6/2 mice up to 25.3%.…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Smith et al (2006) have performed a dose ranging study administering co-enzyme Q 10 (an essential cofactor of the mitochondrial electron transport chain that can act as a potent antioxidant) in R6/2 mice. The treatment was initiated at postnatal day 28 and high doses of co-enzyme Q 10 significantly extended survival in R6/2 mice up to 25.3%.…”
Section: Antioxidantsmentioning
confidence: 99%
“…In one of these studies, R6/2 mice were treated either with remacemide (a low affinity NMDA receptor channel blocker), co-enzyme Q 10 (a lower dose than the one used in the study by Smith et al, 2006, Section 2.7), or a combination of both compounds . Oral administration of remacemide and co-enzyme Q 10 alone (starting at the early age of 21 days) improved the survival of R6/2 mice, by 15.5% and 14.5%, respectively.…”
Section: Inhibition Of Excitotoxicitymentioning
confidence: 99%
“…Although most evidence suggests that huntingtin's toxicity resides in its soluble protein-protein interactions, huntingtin aggregates mark the presence of misfolded mutant huntingtin in vulnerable cell populations and are a hallmark of HD in humans (7) and in genetic in vivo (6,8,9) and in vitro (10) models of HD. Antioxidant and energy buffering compounds, such as coenzyme Q10 (11,12), creatine (13)(14)(15), and cystamine (16,17), which are neuroprotective in HD transgenic mice, significantly reduce huntingtin aggregates. Aggregation occurs in vivo in the presence of expressed polyglutamine-containing proteins, such as huntingtin or huntingtin fragments and adaptation to high-throughput screening has enabled the identification of selective inhibitors (18,19).…”
Section: H Untington's Disease (Hd) Is a Fatal Autosomal Dominantmentioning
confidence: 99%
“…The dosage under clinical trials is currently up to 3,000 mg/day for human use (Ferrante et al, 2005;Levy et al, 2006). For animal study, the dosage was up to 20,000 mg/kg/day as reported by previous researchers (Yang et al, 2005;Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 99%